The making of gender in Egyptian families: A cross-class engagement - Atia, Farah Moataz (AUC Knowledge Fountain, 2015)
In the midst of an unstable political environment, a booming population, and a neoliberal atmosphere, it is impossible not to notice the wide socio-economic disparities in the urban capital of Cairo. ‘Ishash Kum Ghurab, Misr Al-Qadima is clogged with “informal” buildings contained by its old medieval structure (Sims, 2003, p. 6). It has been suggested by Sims (2003, p. 6) that most families residing in this area, where buildings frequently collapse, belong to the lower-income strata of the society. Nevertheless, I have not found it useful nor accurate to assume that the inhabitants of ‘Ishash Kum Ghurab belong to a particular socio-economic categorization. The idea of socio-economic class is fluid and it is not possible to assign families from certain communities to pre-defined class categories. Zamalek, one of Cairo’s most affluent areas, is only a thirty-minute drive away from ‘Ishash Kum Ghurab. Overlooking the Nile, the area hosts a large number of cafes, restaurants, bars, yoga studios, the Cairo Opera House, and is where most embassies are located. Again, while many of the Zamalek residents could be said to belong to the upper-middle and upper classes, it is not possible to assign them a particular pre-determined class category. However, I could not ignore the apparent socio-economic gap among the families I have spoken with in each of those areas, and within this condition of socio-economic disparity, gender as a system of power, with all the meanings attached to it, is continuously produced, reproduced and contested within families. In the light of the above, this thesis looks at the dominant gender ideologies produced within Egyptian families in both areas along with the ways in which they are simultaneously deployed and contested. My motivation to engage in this cross-class exploration is not based on an assumption that families with different socioeconomic conditions hold dramatically different definitions, articulations, and meanings of gender. Rather, the idea of class enables me to engage in a more inclusive and comprehensive exploration of how gender, as a category of difference, is constructed and contested. In line with my initial hypothesis, my research has revealed that families in the two areas do not hold substantially contrasting ideas and understandings of gender. Yet, this cross-class exploration has enabled me to comprehensively explore how various elements tied to the category of class (such as income, survival strategies, neighborhood dynamics and exposure to dominant modernist narratives) influence how gender is produced, reproduced, upheld and challenged in those two areas. This thesis entails comprehensive interviews with five women and three men from each of the two areas in which the intricate gendered power relations within the family are carefully explored and analyzed. Importantly, through employing ethnographic research focusing on families in two socio-economically distinct areas, this thesis attempts to fill a critical research gap as most (if not all) ethnographies on the Egyptian household tend to solely focus on lower-income communities.